2014
DOI: 10.1042/bj20140196
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating covalent and allosteric effects into rate equations: the case of muscle glycogen synthase

Abstract: Several enzymes have been described that undergo both allosteric and covalent regulation, but, to date, there exists no succinct kinetic description that is able to account for both of these mechanisms of regulation. Muscle glycogen synthase, an enzyme implicated in the pathogenesis of several metabolic diseases, is activated by glucose 6-phosphate and inhibited by ATP and phosphorylation at multiple sites. A kinetic description of glycogen synthase could provide insight into the relative importance of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In yeast, the glycogen shunt also provides an important homeostatic function. By storing excess G6P, which accumulates due to the sudden large increase in glucose, it buffers the G6P pool, similar to what we have observed with insulin-stimulated muscle glycogen synthesis (31,32). ATP homeostasis is maintained, and therefore the turbo effect is prevented (35), by the match between ATP consumption and production.…”
Section: Potential Role Of Futile Cycling At Fbpase In Maintaining Fbpsupporting
confidence: 64%
See 1 more Smart Citation
“…In yeast, the glycogen shunt also provides an important homeostatic function. By storing excess G6P, which accumulates due to the sudden large increase in glucose, it buffers the G6P pool, similar to what we have observed with insulin-stimulated muscle glycogen synthesis (31,32). ATP homeostasis is maintained, and therefore the turbo effect is prevented (35), by the match between ATP consumption and production.…”
Section: Potential Role Of Futile Cycling At Fbpase In Maintaining Fbpsupporting
confidence: 64%
“…2 and the mass balance and steady-state equations shows that the glycogen shunt, consistent with the activation of yeast GS by G6P (29), takes up excess G6P that would otherwise accumulate due to the mismatch of the HK and PK segments of the pathway. We (30,31) and others (32) have shown that glycogen synthesis in muscle similarly prevents G6P accumulation in mammalian muscle when glucose entry is increased rapidly by high postmeal insulin levels. The importance of the homeostatic role of the glycogen shunt has been shown dramatically in yeast by a lethal mutant of the cif1 gene (33) that led to cell death in a glucose medium despite normal enzymatic activity in the glycolytic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the flux values after adaptation are often primarily determined by nongenomic mechanisms, such as allosteric activation and inhibition of enzymes (11,12), and posttranslational enzyme modifications (13), such as phosphorylation (14,15). Similar conclusions have been reached regarding mammalian glucose and mitochondrial metabolism (16)(17)(18)(19). However, while in these systems, the primary adaptations in flux are driven by the initial metabolic phenotype, the accompanying widespread changes in gene expression remain largely unexplained.…”
Section: Significancementioning
confidence: 84%
“…Unlike an operon-type pathway, which cannot reach its maximum metabolic flux for many minutes due to the need to raise enzyme activities by gene expression, Crabtree yeast can reach their maximum rate of glucose metabolism soon after glucose exposure. It is one of many examples in unicellular organisms (22) and multicellular organisms (16)(17)(18)(19) in which metabolic pathways can respond rapidly to a change in environment prior to a change in gene expression. Although specific to yeast, it is relevant to a wide range of organisms, including mammals, for it involves the coregulation of the ubiquitous glycolytic, gluconeogenic, and glycogen-synthesis pathways that play a central role in glucose metabolism.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation